The Dynamic Nature of Hypertrophic and Fibrotic Remodeling of the Fish Ventricle - Keen, Adam N.; Fenna, Andrew J.; McConnell, James C.; Sherratt, Michael J.; Gardner, Peter; Shiels, Holly A. (Frontiers in Physiology, 2016)
Chronic pressure or volume overload can cause the vertebrate heart to remodel. The hearts of fish remodel in response to seasonal temperature change. Here we focus on the passive properties of the fish heart. Building upon our previous work on thermal-remodelling of the rainbow trout ventricle, we hypothesized that chronic cooling would initiate a fibrotic cardiac remodelling, with increased myocardial stiffness, similar to that seen with pathological hypertrophy in mammals. We hypothesized that, in contrast to pathological hypertrophy in mammals, the remodelling response in fish would be plastic and the opposite response would occur following chronic warming. Rainbow trout held at 10 °C (control group) were chronically (> 8 weeks) exposed to cooling (5 °C) or warming (18 °C). Chronic cold induced hypertrophy in the highly trabeculated inner layer of the fish heart, with a 41 % increase in myocyte bundle cross-sectional area, and an up-regulation of hypertrophic markers. Cold acclimation also increased collagen deposition by 1.7-fold and caused an up-regulation of collagen promoting genes. In contrast, chronic warming reduced myocyte bundle cross-sectional area, expression of hypertrophic markers and collagen deposition. Functionally, the cold-induced fibrosis and hypertrophy were associated with increased passive stiffness of the whole ventricle and with increased micromechanical stiffness of tissue sections. The opposite occurred with chronic warming. These findings suggest chronic cooling in the trout heart invokes a hypertrophic phenotype with increased cardiac stiffness and fibrosis that are associated with pathological hypertrophy in the mammalian heart. The loss of collagen and increased compliance following warming is particularly interesting as it suggests fibrosis may oscillate seasonally in the fish heart, revealing a more dynamic nature than the fibrosis associated with dysfunction in mammals.